Blood-Glucose Levels of Rats Given High-Fat Diets after Administration of Neem Leaf Ethanolic Extract - Isdadiyanto, Sri; Mardiati, Siti Muflichatun; Sitasiwi, Agung Janika (Biosaintifika: Journal of Biology & Biology Education, 2021)
Azadirachta indica A. Juss (Neem) is a medicinal plant that contains antioxidants, antihyperlipidemia, and has antidiabetic activity. This research aimed to examine the effect of neem leaf ethanolic extract on blood glucose levels of white rats given high-fat rations. The male white rats (Rattus norvegicus L.) with two months of age were used. The treatment of test animals consisted of six treatment groups and four replications, namely: the control group (P0); given high fat rations + duck egg yolk 2.5 ml/200gBW (P1); given high-fat rations + 8 mg/200gBW simvastatin (P2); and P1+ the dose of neem leaf ethanolic extract of 75; 100; and 125 mg/200gBW (P3; P4; and P5). Blood-glucose levels were analyzed by colorimetric enzymatic method using Roche Diagnostics Cobas C reagents kits. Blood-glucose level was determined using Roche / Hitachi cobas c systems automatically. Homogeneous and normally distributed data of blood-glucose levels, body weight and feed consumption were analyzed statistically using ANOVA followed by Duncan's test with a significance level of 5% using SPSS 16.0 software. The results indicated that giving the neem leaf ethanolic extract of could reduce the blood glucose levels. In this study, it was concluded that the neem leaf ethanolic extract of could potentially be used as an alternative to cure diabetes mellitus.